Vpu Exploits the Cross-Talk between BST2 and the ILT7 Receptor to Suppress Anti-HIV-1 Responses by Plasmacytoid Dendritic Cells. - Mariana G Bego; Édouard Côté; Nick Aschman; Johanne Mercier; Winfried Weissenhorn; Éric A Cohen (PLoS Pathogens, 2015)
Plasmacytoid dendritic cells (pDCs) constitute a major source of type-I interferon (IFN-I) production during acute HIV infection. Their activation results primarily from TLR7-mediated sensing of HIV-infected cells. However, the interactions between HIV-infected T cells and pDCs that modulate this sensing process remain poorly understood. BST2/Tetherin is a restriction factor that inhibits HIV release by cross-linking virions onto infected cell surface. BST2 was also shown to engage the ILT7 pDC-specific inhibitory receptor and repress TLR7/9-mediated IFN-I production by activated pDCs. Here, we show that Vpu, the HIV-1 antagonist of BST2, suppresses TLR7-mediated IFN-I production by pDC through a mechanism that relies on the interaction of BST2 on HIV-producing cells with ILT7. Even though Vpu downregulates surface BST2 as a mean to counteract the restriction on HIV-1 release, we also find that the viral protein re-locates remaining BST2 molecules outside viral assembly sites where they are free to bind and activate ILT7 upon cell-to-cell contact. This study shows that through a targeted regulation of surface BST2, Vpu promotes HIV-1 release and limits pDC antiviral responses upon sensing of infected cells. This mechanism of innate immune evasion is likely to be important for an efficient early viral dissemination during acute infection.